Relevance of Interleukins 6 and 8 Single Nucleotide Polymorphisms in Prostate Cancer: A Multicenter Study. (6th July 2021) - Ghazy, Amany A.; Alenzi, Mohammed Jayed
Abstract : The diverse roles of cytokines as IL-6 and IL-8 have been studied in terms of their SNPs in many diseases but their role in prostate cancer (PCa) is still uncertain. Aim . To determine the relevance of IL-6 rs1800795 SNP and/or IL-8 rs2227306 SNP with prostate cancer's risk. Subjects and Methods . 40 PCa patients, 40 benign prostate hyperplasia (BPH) patients, and 40-age-matched-control group were enrolled in the study. Genotyping of IL-6 rs1800795 (G/C) SNP and IL-8 rs2227306 (C/T) SNP was determined using real-time PCR. Results . High frequency of IL-6 rs1800795GG and IL-8 rs2227306CC genotypes was noticed among PCa patients with associated OR 10.091 and 8.143, respectively. Comparisons based on allele frequencies revealed that IL-6G and IL-8C alleles are more frequent among PCa patients than other groups. Presence of IL-6 rs1800795G and IL-8 rs2227306C alleles in the same patient increase PCa risk by 16.7 times. Statistical correlations between PSA ratio and both of IL-6 and IL-8 SNP did not show any significant relation among PCa patients. Conclusion . IL-6 rs1800795G and IL-8 rs2227306C alleles could be considered risk factors for PCa development, particularly if presented together. However, no relation was found between both cytokines SNP and severity of prostate cancer.